Aktivitas Antioksidan Ekstrak Etanol Dan Fraksinya Dari Kulit Batang Rambutan (Nephelium Lappaceum Linn) Menggunakan Metode DPPH - Sari, Tisa Mandala; Nurdin, Hazli; Putri, Elin Andika (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2020)
The bark of the rambutan plant (Nephelium Lappaceum Linn) is a plant that contains flavonoid compounds that can be used as antioxidants. This study aims to determine the IC50 value of ethanol extract along with fractions of n-hexane, ethyl acetate and n-butanol from rambutan bark. The ethanol extract was obtained by the maceration method using 70% ethanol and then 96% ethanol. The fractionation process uses n-hexane, ethyl acetate, and n-butanol. Testing antioxidant activity using the DPPH method by looking at the IC50 value. The results showed that ethanol extract obtained IC50 of 24.21 ppm, n-hexane fraction of 3149.84 ppm, ethyl acetate fraction of 9.05 ppm, the n-butanol fraction of 19.74 ppm and gallic acid as a comparison of 2.27 ppm. The greater the IC50 value, the weaker the antioxidant activity will be. Based on this value, ethanol extract, ethyl acetate fraction and n-butanol fraction have very strong antioxidant activity that is <50 ppm. Whereas the n-hexane fraction has weak antioxidant activity (> 150 ppm). The conclusion that the antioxidant activity of rambutan stem bark belongs to the very strong category in ethanol extract, ethyl fraction and varying n-butanol fraction. But in the n-hexane fraction, values ​​are included in the weak category. It is recommended that the results of this study be continued in the manufacture of pharmaceutical preparations such as in cosmetics.